Gastrointestinal Helminth Parasites of the fish Synodontis clarias (Siluriformes: Mochokidae) from Lekki lagoon, Lagos, Nigeria - Akinsanya, B.; A. Hassan, A.; O. Adeogun, A. (Revista de Biología Tropical, 2008)
A total of 362 specimens of the fish Synodontis clarias were randomly selected and subjected to parasitological examination for helminth parasites. They were collected over a period of one year from Lekki lagoon, Lagos, Nigeria. The prevalence of gastrointestinal infection was 38.7%. The helminth worms found include two cestodes, Proteocephalus spp., Wenyonia acuminata, and a nematode species, Raphidascaroides. Male specimens (196) presented a higher rate of infection (37.8%) than female specimens (166) which showed a rate of 23.5%. The overall worm burden was high (678) and it was independent of fish sex and fish size.